2010
DOI: 10.3109/08941930903469367
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Butyrate on the Healing of Colonic Anastomoses in Rats

Abstract: This experiment suggests that butyrate has a significant role in increasing the mechanical strength of colonic anastomoses in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Since then, butyrate enemas have popularly been used as medicaments stemming from their potential to impart beneficial attributes to the colon. This potential involves an increase in mechanical strength of injured colonic mucosa to hasten the healing process (Bloemen et al, 2010;Mathew et al, 2010), suppression of IL-8 production by intestinal epithelial cells to protect against the inflammatory process (Malago et al, 2005), and clinical remission of UC by protecting against inflammatory and oxidative stress parameters of the disease (Hamer et al, 2010b). Much as butyrate tends to impart a protective effect, several authors have indicated failures or limited success of butyrate to relieve IBD patients (Harig et al, 1989;Sanderson, 1997;Hamer et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, butyrate enemas have popularly been used as medicaments stemming from their potential to impart beneficial attributes to the colon. This potential involves an increase in mechanical strength of injured colonic mucosa to hasten the healing process (Bloemen et al, 2010;Mathew et al, 2010), suppression of IL-8 production by intestinal epithelial cells to protect against the inflammatory process (Malago et al, 2005), and clinical remission of UC by protecting against inflammatory and oxidative stress parameters of the disease (Hamer et al, 2010b). Much as butyrate tends to impart a protective effect, several authors have indicated failures or limited success of butyrate to relieve IBD patients (Harig et al, 1989;Sanderson, 1997;Hamer et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…24 This was corroborated by another group which similarly found strengthened bursting wall tension in those subjects receiving butyrate enemas postoperatively after right and left colon resection. 25 To look at this pathophysiology further, Levison demonstrated that SCFAs inhibited in vitro growth of P. aeruginosa 26 exactly the pathogen that was later identified as being able to transform into tissue destroying phenotype with high collagenase activity, as previously discussed. 18 Taken together, it tends to reason that the gut microbiome may additionally influence anastomotic healing by production of SCFAs, namely butyrate, which have beneficial effects on anastomotic integrity, and possibly limiting the growth of deleterious bacterial pathogens.…”
Section: Butyratementioning
confidence: 93%
“…Previous animal studies have shown that rectal administration of butyrate—one of the predominant short chain fatty acids (SCFAs)—results in a higher bursting pressure in colonic anastomoses, thereby claiming an enhanced strength which may prevent anastomotic leakage [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%